Dinamika Keamanan dan Demokrasi di Indonesia - Huriyah, Syarifah; Hazyimara, Karunia; Zuhairah, Syarifah (Sanger Journal: Social, Administration and Government Review, 2024)
This article discusses the challenges faced by the South Sulawesi Police in the context of the dynamics of security and democracy in Indonesia ahead of the 2024 Regional Head Elections (Pilkada). The post-Cold War era and the rise of new global powers have influenced the democratization process in various countries, including Indonesia, which has experienced a significant democratic transition after the 1998 Reformation. However, this process also presents challenges such as radicalization, social polarization, and conflict that are often exploited by political actors. In the scientific oration of the South Sulawesi Police Chief at the 107th Graduation Ceremony of UIN Alauddin Makassar with the theme "Challenges of the Police in Facing the Era of Democracy (Pilkada Era), the importance of community policing and proactive policing approaches in maintaining security stability and preventing social conflict was emphasized. This study uses a descriptive qualitative method with literature study and analysis of oration texts to identify the main challenges faced by the Police. The results of the study indicate that geopolitical changes, social inequality, and potential conflicts due to sensitive issues are factors that need to be addressed. This article recommends improving political education, community involvement, and conflict mitigation strategies to create a healthy and stable democratic climate in Indonesia.